Oral administration of the selective GPR120/FFA4 agonist compound A is not effective in alleviating tissue inflammation in mouse models of prototypical autoimmune diseases. Issue 6 (8th November 2018) - Wannick, Melanie; Bezdek, Siegfried; Guillen, Nathalie; Thieme, Markus; Meshrkey, Fibi; Mousavi, Sadegh; Seeling, Michaela; Nimmerjahn, Falk; Mócsai, Attila; Zillikens, Detlef; Sezin, Tanya; Sadik, Christian D.
Abstract: ω3‐polyunsaturated free fatty acids (ω3‐PUFAs), particularly docosahexaenoic (DHA) and eicosapentaenoic acid (EPA), are thought to exert health promoting effects in metabolic and in inflammatory diseases. The molecular mechanisms of these beneficial effects are only partially understood. DHA and EPA activate Free Fatty Acid receptor 4 (GPR120/FFA4). Recently, the first orally available, synthetic ligand of FFA4, 3‐[2‐chloro‐5‐(trifluoromethoxy)phenyl]‐3‐azaspiro[5.5]undecane‐9‐acetic acid ("compound A"; cpd A) has been developed. Cpd A exhibits distinctly higher potency, efficiency, and selectivity at FFA4 than ω3‐PUFAs and ameliorates insulin resistance and adipose tissue inflammation in the mouse. With GPR120/FFA4 activation believed to also attenuate tissue inflammation in autoimmune diseases, cpd A may also have a beneficial effect in these diseases. We have therefore addressed the therapeutic potential of cpd A in mouse models of three prototypical autoimmune diseases, specifically psoriasis, rheumatoid arthritis, and bullous pemphigoid. The effect of cpd A on the course of Aldara™‐induced psoriasis‐like dermatitis, K/BxN serum transfer arthritis, and antibody transfer pemphigoid disease‐like dermatitis was scrutinized. Cpd A did not alter the course of Aldara‐induced psoriasis‐like dermatitis, K/BxN serum transfer arthritis, or antibody transfer pemphigoid disease‐like dermatitis. Our results suggest that therapeutic regimens solely relying on FFA4 activation do not bear the potential to treat inflammatory diseases. With cpd A distinctly more potent in activating GPR120/FFA4 than ω3‐PUFAs, this also suggests that GPR120/FFA4 activation by ω3‐PUFAs does not significantly contribute to the health‐promoting effects of ω3‐PUFAs in autoimmune diseases.